Serum β-amyloid 1–42 Levels as Alternative Non-invasive Screening Biomarker for Alzheimer’s Disease and Vascular Dementia in Indonesian Elderly Population - Indah Aprianti Putri; Huda Shalahuddin Darusman; Muhammad Hamdan; Pukovisa Prawiroharjo; Budi Utomo; Jusak Nugraha; Yohanna Kusuma; Nurrani Mustika Dewi; Ferry Sandra (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Alzheimer’s disease (AD) and vascular dementia (VaD) impose a substantial public health burden in Indonesia; however, accessible blood-based biomarkers for early screening remain limited. Although cerebrospinal fluid β-amyloid 1–42 is an established biomarker, its invasive nature restricts its use for population-level screening. Therefore, it is necessary to have locally-produced serum β-amyloid 1–42 ELISA kit that is specifically designed for Indonesian elderly population. In this study, a locally-produced β-amyloid 1–42 ELISA kit was validated and used for the screening of AD, VaD and mild cognitive impairment (MCI) Indonesian population.METHODS: A cross-sectional study including 166 subjects: 31 AD, 34 VaD, 34 MCI patients, and 67 cognitively normal controls was conducted. All participants underwent cognitive assessments including Mini Mental State Examination (MMSE) and Montreal Cognitive Assessment-Indonesian version (MoCA-Ina), as well as brain magnetic resonance imaging (MRI) 3-Tesla for the assessment of medial temporal atrophy/white matter changes. Fasting venous blood sampling was taken from each subjects for the measurement of serum β-amyloid 1-42 measurement using locally-produced ELISA kit.RESULTS: Median serum β-amyloid 1–42 levels were 11.03, 10.99, and 10.99 pg/mL for the AD, VaD, and MCI subjects, respectively. The β-amyloid 1–42 levels were correlated with MMSE scores in all group (AD: r=−0.455, p=0.010; VaD: r=−0.419, p=0.014; MCI: r=−0.412, p=0.015). The validity analysis of the locally-produced serum β-amyloid 1–42 ELISA kit, showed sensitivity of 94.12% (95% CI: 87.3–97.9), specificity of 80.36% (95% CI: 72.4–86.8), and diagnostic accuracy of 83.56% (95% CI: 77.2–88.5).CONCLUSION: Serum β-amyloid 1–42 levels are lower in AD and VaD subjects compared to MCI and control subjects. Serum β-amyloid 1-42 is inversely correlated with cognitive function across all groups based on MMSE score. Additionally, the locally-produced β-amyloid 1-42 ELISA kit demonstrated sensitivity of 94.12% and specificity of 80.36%, meeting Global CEO Initiative Consensus for pre-screening tools, supporting its potential as a scalable, non-invasive screening biomarker in Indonesian primary care settings.KEYWORDS: G-banding karyotyping, next generation sequencing, non-invasive prenatal testing